2015
DOI: 10.4172/2161-0932.1000316
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Steroid Cell Tumor Associated to Endometrial Hyperplasia and Presenting as Postmenopausal Vaginal Bleeding

Abstract: Background: Ovarian Steroid cell tumor is a subtype of sex-cord stromal tumor which is very infrequent. It is usually benign and unilateral and causes hyperandrogenism and virilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Her initial assessment with ultrasonography showed endometrial thickness of 15 mm, indicating hyperestrogenism. Monappa V et al [2] and Rubio et al [8] have reported similar cases of postmenopausal woman of SLCT with features of hyperestrogenism.…”
Section: Discussionmentioning
confidence: 87%
“…Her initial assessment with ultrasonography showed endometrial thickness of 15 mm, indicating hyperestrogenism. Monappa V et al [2] and Rubio et al [8] have reported similar cases of postmenopausal woman of SLCT with features of hyperestrogenism.…”
Section: Discussionmentioning
confidence: 87%
“…However, approximately a third of these tumors may exhibit malignant behavior. Hayes and Scully ( 1 ) defined five pathological predictive characteristics of the malignant behavior of these tumors: size >7 cm; >2 mitoses/10 high-power fields; necrosis; hemorrhage; and grade 2–3 nuclear atypia ( 11 , 12 ). Immunohistochemically, inhibin and calretinin are considered sensitive markers for diagnosing steroid cell tumors.…”
Section: Discussionmentioning
confidence: 99%